MODEL MANAJEMEN BERBASIS SOLUSI MENGATASI KEKURANG STANDARAN DALAM PENGELOLAAN HUBUNGAN SEKOLAH DAN PEMBERDAAYAAN MASYARAKAT DI SMP NEGERI REMBAN KABUPATEN MUSI RAWAS UTARA - Fitriyani Fitriyani (El-Ghiroh : Jurnal Studi Keislaman, 2018)
the relationship between SMP Negeri Remban and the surrounding community is still not well established. Where the public attention to the school is still very minimal, whereas SMP Negeri Remban is the only junior school owned by the village. From the results of this obeservasi, the authors are interested to conduct research at the school by implementing the "Solution-Based Management Model To Overcome The Minimal In Management Of School Relations And Public Awareness.